دراسة مقارنة بين ثلاثة فحوص تشخيصية للإصابة بالحلزونية البوابية - انطانيوس ميلاد (Latakia University Journal -Medical Sciences Series, 2019)
الحلزونية البوابية جرثومة ممرضة تصيب الإنسان فقط فتسبب التهاب معدة مزمناً، لها دور أساسي في إحداث القرحات المعدية الاثني عشرية، والآفات التنشؤية المعدية، كما تلعب دوراً ً في إحداث أعراض عسر الهضم. الالتهاب المعدي المزمن الذي تحدثه الإصابة بالحلزونية البوابية يستمر عادة مدى الحياة وهو من أكثر الالتهابات الجرثومية انتشاراً في العالم حيث تصيب من 40% إلى 50% من البشر في البلدان المتطورة، و 80-90% من البشر في البلدان النامية. تشخيص الإصابة بالحلزونية البوابية هو المرحلة الأساسية قبل المعالجة. هذا التشخيص يتم إما بعد اللجوء إلى تداخل (تنظير هضمي) على المريض ومنه أخذ عينة أو خزعة من مخاطية المعدة أو غير تداخلي (لا يحتاج إلى تنظير هضمي). في دراستنا قمنا بالمقارنة بين نتائج ثلاثة فحوص تشخيصية للإصابة بالحلزونية البوابية هي: - اختبار خميرة البولة السريع. - التحري النسجي المباشر للحلزونية البوابية. - الفحص المصلي لاضاد للحلزونية البوابية. من خلال دراسة 79 مريضاً عرضياً لديهم بالتنظير الهضمي قرحة معدية, التهاب معدة تقرحي، قرحة اثنى عشرية, التهاب بصلة تقرحي، سرطان معدي غدي. Helicobacter pylori is a human pathogen that causes chronic gastritis, has a role in gastric and duodenal ulcer, is involved in gastric carcinogenesis, and is regarded as a possible important factor in at least a subset of patients with functional dyspepsia. Helicobacter pylori causes a chronic gastric infection that is usually lifelong, and many epidemiologic studies have shown that this is probably one of the most common bacterial infection throughout the world involving 40% to 50% of population in developed countries and 80% to 90% of population in developing countries. The diagnostic of helicobacter pylori infection represents a key step before the management of infection. Helicobacter pylori can be diagnosed by invasive (require endoscopy) and non-invasive techniques (not require endoscopy) each of the available diagnostic techniques has advantages and disadvantages. In our study, we compared between results (positive and negative) of three diagnostic tests of helicobacter pylori –rapid urease test, histological diagnostic study, and serological diagnostic study throughout the application of this tests at 79 symptomatic patients needed diagnostic endoscopy. We found at them gastric ulcer, erosive gastritis, duodenal ulcer, erosive duodenatitis, and gastric adenocarcinoma.